(untitled) (Medicine Today, 2017)
Ear foreign body is a common ENT emergency and a challenge also to otolaryngologist worldwide. Prompt and appropriate management of it can reduce the morbidity. An observational retrospective study of 148 cases of foreign body in the ear done in Comilla Medical College Hospital and two upazilla health complexes (Nangalkot and Chowddagram) of Bangladesh within the period of January 2014 to December 2014 to evaluate the nature, mode of presentation, technique of removal and outcome of it. Data were collected from hospital records including age, sex of patient and mode and time of presentation, nature of foreign body, management outcome and complication, and the result showed that children o funder 15 year age group were mostly affected (60%), among them highest incidence were in 5-10 year age group (25%) with male to female ratio 1:1.28. The most common foreign body was the seeds of various vegetables (25.67%) followed by plastic beads (18.24%) and cotton bud (15.54%), the right ear affected more (54%). Almost half of them (47.97%) presented with history of insertion of a foreign body and most of them (91.98%) were removed in OPD or emergency department under direct vision and remaining required general anesthesia. Despite a high proportion of cases managed in the office setting, complication rates were within acceptable level. It is inversely proportional to the skill of the personnel, number of attempts &availability of equipment. Key to successful outcome are prompt help by well-trained doctor and otolaryngological equipment set up. Medicine Today 2017 Vol.29(2): 5-8